ANALISIS EKONOMI RUMAH TANGGA TANI SAYURAN DI DESA PANDANSARI KECAMATAN PAGUYANGAN KABUPATEN BREBES - , ARINDA NUR IVANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to determine farm income and its contribution to total household income, determine the level of poverty and welfare of vegetable farmers, analyses household time allocation to farming activities, and determine factors that influence household time allocation to farming activities in Pandansari village Paguyangan subdistrict of Brebes Regency. The basic methode that used in this research was a descriptive analytical method. This research was carried out in Pandansari Village located in Paguyangan Subdistrict of Brebes Regency. Determination of sample village was conducted using purposive sampling method whereas farmers using simple random sampling method. The result of data analysis shows that the cotribution of farm income to total household income is 61,46%. Its shows that farm income is the main source of income for farm households. Based on the analysis of the proverty level according to the criteria Sayogyo, BPS of Brebes Regency, and the World Bank farm household is nonpoor. While the analysis based on the welfare that use GSR farm household relatively prosperous. Farm household time allocation to farming activities is 1.316,30 hours/year. The factors that influence household time allocation to farming activities is land area. The R2 value is 0,756 meaning that the contribution of independent variable (land area, farm income, number of family members, wage labor) to the variation of household time allocation to farming activities is 75,6%, while 24,4% remaining is affected by other variables excluded from the model. The result of F test and t test shows that land area variable affect significantly the household time allocation to farming activities at significance level of 99%. While farm income, number of family members, wage labors variables affect not significantly the household time allocation to farming activities.